RM1mil boost for UPM's Coffers - The Sun, Kristene Silva Marie (2009)
Universiti Putra Malaysia (UPM) recently received RM1 million from Asiatic Development Sdn Bhd to fund its research and educational programmes, and to grant scholarships under the name of late businessman and tycoon Tan Sri (Dr) Lim Goh Tong.